ISOLASI DAN IDENTIFIKASI FUNGI DI SEKITAR POHON PENGHASIL GAHARU (Gyrinops versteegii) DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS SENARU LOMBOK UTARA - Ahsanu Nadia; Tri Mulyaningsih (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2026)
The high market value of agarwood has a significant impact on its marketing. Extracts from agarwood (Gyrinops versteegii) stems contain alkaloids, terpenoids, and tannins that can act as antibacterials, antioxidants, anticancer, and antifungal agents. This study used the fungus trap method to identify fungi found around the agarwood-producing Gyrinops versteegii tree. The identified fungi comprised five genera and eight species: Acremonium, Aspergillus, Fusarium, Mucor, and Rhizopus.